Representasi Makanan Nusantara dalam Kumpulan Puisi Sarinah Karya Esha Tegar Putra: Tinjauan Gastrokritik - Agus Sulton; Aditya Ardi Nugroho (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2022)
This study aims to describe the food of the archipelago in the collection of poetry Sarinah by Esha Tegar Putra with a gastrocritical approach. The research method used is descriptive qualitative research method. The data source in this study is a collection of Sarinah poems by Esha Tegar Putra published by the publisher PT Grasindo, Jakarta in 2016. The data in this study are in the form of words and sentences in a collection of Sarinah poems by Esha Tegar Putra which represent elements of gastronomy or Nusantara food in poetry. The data collection and research process was carried out with the following steps: (1) reading the data was done by reading the entire contents of the data source, namely a collection of Sarinah poems by Esha Tegar Putra; (2) identify data that represents the gastronomic elements or food of the archipelago in the Sarinah poetry collection by Esha Tegar Putra; (3) codifying data to facilitate the process of data analysis; (4) analyzing data by displaying data quotes and then analyzing it using a gastrocritical approach; (5) draw conclusions. The results of this study indicate that in the collection of poetry Sarinah by Esha Tegar Putra there is a representation of Indonesian food.